The Effect of Quality of Education and School Facilities on the Decision to Choose SMP PAB 15 Medan Sunggal - Anggiat Maruba Sihombing (Outline Publisher, 2022)
This study aims to determine the effect of Education Quality on the Decision to Choose SMP PAB 15 Medan Sunggal, find out the influence of School Facilities on the Decision to Choose SMP PAB 15 Medan Sunggal, find out the influence of Quality of Education and School Facilities on the Decision to Choose SMP PAB 15 Medan Sunggal. The research population that will be used in the study is all students of SMP PAB 15 Medan for the 2019/2020 to 2021/2022 academic year with a total of 212 students. Using the Slovin formula with an error rate of 5%, a total sample of 139 respondents was obtained. The results showed that the Quality of Education and School Facilities partially had a positive and significant effect on the Decision to Choose SMP PAB 15 Medan Sunggal. The results showed that the quality of education and school facilities simultaneously had a positive and significant effect on the decision to choose SMP PAB 15 Medan Sunggal. The results of this study are supported by the value of R square (R2). While the rest is influenced by other factors that come from outside this research model such as service, price, promotion, and other variables.